Serum p-Glycoprotein and Monomeric C-Reactive Protein are Elevated in Takayasu Arteritis - Thakare DR; Singh K; Qamar T; Singh D; Balakrishnan S; Rathore U; Jain N; Ora M; Misra DP (Dove Medical Press, 2024)
Darpan Radheshyam Thakare,1,2,* Kritika Singh,1,* Tooba Qamar,1 Deeksha Singh,1 Sandeep Balakrishnan,1 Upendra Rathore,1 Neeraj Jain,3 Manish Ora,4 Durga Prasanna Misra1 1Department of Clinical Immunology and Rheumatology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, India; 2Department of Clinical Immunology and Rheumatology, King George Medical University (KGMU), Lucknow, Uttar Pradesh, India; 3Department of Radiodiagnosis, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, India; 4Department of Nuclear Medicine, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, Uttar Pradesh, India*These authors contributed equally to this workCorrespondence: Durga Prasanna Misra, Department of Clinical Immunology and Rheumatology, Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, 226014, Uttar Pradesh, India, Email durgapmisra@gmail.com; dpmisra@sgpgi.ac.inPurpose: Existing biomarkers including C-reactive protein (CRP) do not adequately distinguish active and inactive TAK. We compared serum p-glycoprotein (p-gp)/Multidrug Resistance Protein 1 (MDR1), monomeric CRP (mCRP), CRP, and mCRP:CRP ratio in Takayasu arteritis (TAK) and healthy controls and their relationship with disease activity.Patients and Methods: Serum p-gp mCRP (ELISA) and CRP (nephelometry) were compared between consecutive adults with TAK (> 18 years) enrolled from a prospective cohort (n = 92) and healthy controls (n = 29), and between active vs inactive TAK (n = 46 each). In a subset of active immunosuppressive-naïve TAK (n = 29), correlation was assessed between serum p-gp and p-gp expression on circulating T helper lymphocyte populations: overall (CD4+), Th17 (CD4+IL-17+), Th17.1 (CD4+IL-17+IFN-γ+) lymphocytes [normalized to Tregs (CD4+CD25+FoxP3+)]. Changes in serum p-gp, mCRP, CRP, and mCRP:CRP were compared before and after immunosuppression (n = 29). Data was represented using median (Q1-Q3). Receiver operating characteristics (ROC) curves were generated for TAK vs controls, and active vs inactive TAK with serum p-gp, mCRP, CRP, and mCRP:CRP. Multivariable-adjusted linear regression was used to predict active disease with serum p-gp, mCRP, CRP, or mCRP:CRP.Results: Serum p-gp (11.19 vs 8.05 ng/mL), mCRP (1.61 vs 1.25 μg/L), and CRP (5.40 vs 2.1 mg/L) were elevated in TAK vs controls (p < 0.05 for all). CRP was higher and mCRP:CRP ratio was lower in active vs inactive TAK (p < 0.001). ROC curves identified moderate prediction for active disease with CRP and inactive disease with serum p-gp (area under ROC curve 0.705 and 0.392, respectively). Multivariable-adjusted linear regression confirmed association of CRP with active disease (p = 0.009) and serum p-gp with inactive disease (p = 0.041). In treatment-naïve TAK, serum p-gp negatively correlated with p-gp+Th17.1 lymphocytes (Spearman's rho=− 0.39, p = 0.046). CRP and serum p-gp were significantly lowered following immunosuppressive therapy in treatment-naïve TAK (p < 0.05).Conclusion: Serum p-gp and mCRP are elevated in TAK. Serum p-gp is associated with inactive disease.Keywords: Takayasu arteritis, MDR1 protein, C-reactive protein, large vessel vasculitis, aortoarteritis, disease activity